The Relationship Between the Big Five Personality Factors and the Intention of Corruption - Modesto, João Gabriel (2021)
Corruption must be investigated from different levels of analysis. At the intra-individual level, personality is a relevant variable for its understanding. Objective. In the present research, we sought to analyze the influence of personality traits on the intention of corrupt behavior based on the Big Five model of personality. Method. This study included 286 individuals between the ages of 18 and 76. A Reduced Scale of the Big Five personality factors, and a Corruption Intention Measurement scale, along general sociodemographic data were part of the data collection process. Results. Data showed positive correlations between corruption intention and the dimensions of agreeableness, conscientiousness, and openness. However, using multiple linear regression, only conscientiousness had a significant effect. Implications are discussed.